2021
DOI: 10.3390/su131911115
|View full text |Cite
|
Sign up to set email alerts
|

Generic Digital Equity Model in Education: Mobile-Assisted Personalized Learning (MAPL) through e-Modules

Abstract: This study addresses the challenges most learners face in Third World and developing countries concerning education accessibility in an emergency. On the basis of the shortcomings found in a review of past studies, this scoping review introduces adapted model mobile-assisted personalized learning (MAPL), which focused on full distance learning using the personalized learning (PL) concept. This concept is rarely used in the classrooms of Third World and developing countries. MAPL is technology-integrated and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…For example, Sayuti, et al (2020) reported that learners' lack of confidence in speaking during a virtual class made them uncomfortable during interaction hours. In addition, unprivileged learners may confront various problems when following online lessons, such as poor Internet access and insufficient devices for distant-learning (Song et al, 2021). Moreover, learners with mixed abilities have problems in catching up with their peers as teachers provide standardised tasks in an online language classroom.…”
Section: B Online Esl Learningmentioning
confidence: 99%
“…For example, Sayuti, et al (2020) reported that learners' lack of confidence in speaking during a virtual class made them uncomfortable during interaction hours. In addition, unprivileged learners may confront various problems when following online lessons, such as poor Internet access and insufficient devices for distant-learning (Song et al, 2021). Moreover, learners with mixed abilities have problems in catching up with their peers as teachers provide standardised tasks in an online language classroom.…”
Section: B Online Esl Learningmentioning
confidence: 99%
“…According to the results of this study, socio-ecological support significantly influences participation in social activities. Social support, whether from family, peers, the local community or the virtual community, needs to be mobilised to ensure the active participation of the urban community in various activities [46]. This is particularly important because participation in social activities has the highest influence on social well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The growing access to technology has become an important aspect of enhancing language learning in ESL and EFL learners' learning settings. Most educators use technology in their classroom teaching and learning activities because it plays a major role in motivating and enhancing students' language learning [76]. The incorporation of non-textual elements with technology are both supplementary and complementary in nature, supporting ESL and EFL learning outcomes.…”
Section: Discussionmentioning
confidence: 99%